ASPEK HUKUM WAKAF DALAM KAJIAN HADIS AHKAM (Melacak Akar Sejarah Hukum Wakaf Dan Penerapannya di Indonesia) - Muhazir Muhazir (Universitas Islam Negeri Sumatera Utara, 2020)
The waqf hadith in text only describes waqf for immovable objects, in contrast to the current context in Indonesia which wants to develop a broader concept of waqf not just waqf for immovable objects as described in Law Number 41 of 2004 concerning Waqf. The paradigm between the hadith text and application in Indonesia causes a different understanding so that it is necessary to reunderstand the hadith text in its current context. The purpose of this article is to look at legal hadiths about waqf by tracing the history of waqf and its application in Indonesia. The results of the research show that the hadith narrated by Bukhȃri about waqf contained in the Syurȗth chapter with Number 19 is the legal basis for waqf used by the Muslim clergy, in this hadith it only describes the status of waqf objects, while in Indonesia itself the Waqf Law leads to productive waqf and cash.